PEMBUATAN KARAKTER VIRTUAL SEBAGAI PEMANDU DALAM KONTEN VIDEO TUTORIAL MENGGAMBAR - Natan Dwipangga Arisuwito; Hutomo Setia Budi (Universitas Ciputra Surabaya, 2020)
Drawing tutorial become a necessity for people who learn to draw. Drawing tutorial videos can be accessed via YouTube. On the other hand, virtual youtuber become a global trend including in Indonesia where dozens of virtual youtuber channels are popping up. Through this study, researcher designed virtual character which will guide the audiences through drawing tutorial videos on a YouTube channel. The purposes of this study are to find out how to design a virtual character and drawing tutorial which will attract the audiences and to take viewers response to the virtual characters as a guide for drawing tutorial. The research methods used in this study are qualitative and quantitative method. The approaches is carried out by spreading questionnaires, interviewing expert and extreme users and observing competitor. Keyword : virtual youtuber, virtual character, drawing tutorial